2018
DOI: 10.3389/fimmu.2018.02035
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 Receptor Inhibition by Tocilizumab Attenuated Expression of C5a Receptor 1 and 2 in Non-ST-Elevation Myocardial Infarction

Abstract: Background: Elevated interleukin-6 (IL-6) and complement activation are associated with detrimental effects of inflammation in coronary artery disease (CAD). The complement anaphylatoxins C5a and C3a interact with their receptors; the highly inflammatory C5aR1, and the C5aR2 and C3aR. We evaluated the effect of the IL-6 receptor (IL-6R)-antagonist tocilizumab on the expression of the anaphylatoxin receptors in whole blood from non-ST-elevation myocardial infarction (NSTEMI) patients. Separately, anaphylatoxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…Relative levels of RNA transcripts of C3aR (A) and C5aR1 38 are shown as determined from RNA extracts isolated from endothelial cells stimulated with purified C3a or C5a, in comparison to untreated controls. Values are represented as mean ± SE analyzed from three independent experiments run in duplicate test wells, and samples duplicated for the quantitative RT‐PCR analyses (N = 12) 38 . Western blot analysis of activated C3aR (c‐Jun and ETS1) and C5aR1 (NFYA1) transcription factors from HUVECs stimulated with C3a or C5a.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Relative levels of RNA transcripts of C3aR (A) and C5aR1 38 are shown as determined from RNA extracts isolated from endothelial cells stimulated with purified C3a or C5a, in comparison to untreated controls. Values are represented as mean ± SE analyzed from three independent experiments run in duplicate test wells, and samples duplicated for the quantitative RT‐PCR analyses (N = 12) 38 . Western blot analysis of activated C3aR (c‐Jun and ETS1) and C5aR1 (NFYA1) transcription factors from HUVECs stimulated with C3a or C5a.…”
Section: Resultsmentioning
confidence: 99%
“…Western blot analysis of activated C3aR (c‐Jun and ETS1) and C5aR1 (NFYA1) transcription factors from HUVECs stimulated with C3a or C5a. Phosphorylated (activated) pETS1 and pc‐Jun are calculated and depicted in the bar graphs of 38 as phosphorylated proteins/total proteins (see Section 2 for details). Values are represented as mean ± SE analyzed from two independent experiments run in duplicate test wells of the SDS‐PAGE gels (N = 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, studies of coronary artery disease (CAD) found that IL‐6 and complement may both contribute to the progression of cardiovascular diseases. In patients with non‐ST‐elevation myocardial infarction (NSTEMI), IL‐6 inhibition with the anti‐IL‐6R mAb (tocilizumab) reduced C5aR1 and C5aR2 in whole blood along with decrease of C‐reactive protein (CRP) and percutaneous coronary intervention (PCI)‐related troponin T (TnT) release 13 …”
Section: Figurementioning
confidence: 99%
“…In addition, the drugs that affect the adipokines are also being examined as potential therapeutics. [2][3][4][5][6][7][8] A recently identified adipokine, neuregulin-4 (Nrg4), is one of the four neuregulin family proteins: cell-cell signaling proteins that possess an EGF-like domain and bind to the ErbB family tyrosine kinase receptors. 9) Nrg4 was first identified as a neuregulin family protein enriched in the pancreas, 10) but recently Rosell, et al reported that Nrg4 is highly expressed in brown adipose tissues (BAT) as an adipokine; its role in atherosclerosis has been gaining attention.…”
mentioning
confidence: 99%